Targeting Tumor Endothelial Cells by EGCG Using Specific Liposome Delivery System Inhibits Vascular Inflammation and Thrombosis - Zi Jia; Nako Maishi; Hideki Takekawa; Aya Yanagawa Matsuda; Taisei Nakade; Takashi Nakamura; Hideyoshi Harashima; Yasuhiro Hida; Kyoko Hida (Cancer Medicine)
ABSTRACT Background Inflammation is one of the hallmarks of cancer and is associated with tumor growth. Tumor endothelial cells (TECs) demonstrate inflamed phenotypes. Endothelial inflammation initiates thrombus formation, which is the second cause of cancer‐related deaths. Epigallocatechin‐3‐O‐gallate (EGCG), a natural compound in green tea, has demonstrated an anti‐inflammatory effect. However, the tumor progression inhibition effect of EGCG by targeting TEC inflammation remains unclear. This study addresses the anti‐tumor effect of EGCG, especially its anti‐inflammatory role in TECs. Methods In vitro, the effect of EGCG on TECs were studied using real‐time quantitative PCR and immunofluoresence to analyza gene and protein expression. In vivo, a cyclic RGD liposome delivery system (MEND) was employed to efficiently deliver EGCG to TECs in tumor‐bearing mice. Results In vitro, EGCG significantly reduces inflammatory cytokine expression, including tumor necrosis factor‐α, interleukin‐6, IL‐8, and IL‐1β through NF‐κB signaling inhibition. Additionally, von Willebrand factor reduction in TECs, which is involved in platelet adhesion and thrombosis formation, was analyzed. Our results revealed that EGCG‐MEND significantly inhibited TEC inflammation and thrombus formation in tumors. Additionally, EGCG‐MEND improved tumor immunity by reducing programmed death‐ligand 1 expression and promoting high endothelial venule formation by recruiting CD8+ T cells. Conclusion Our results indicate the anti‐tumor potential of EGCG‐MEND in normalizing the inflammatory immune microenvironment and inhibiting thrombosis by targeting TEC.